A selective review of inhibitors of protein kinase C gamma: a neuroplasticity-related common pathway for psychiatric illness - Grados, Marco; Salehi, Mona; Lotfi, Aida; Dua, Sagar; Xie, Isabella (Frontiers in Drug Delivery, 2024)
Psychotropics are currently developed and marketed with a limited understanding of their mechanism of action. The notion that protein kinase C (PKC) activity is highly relevant to learning and memory function stems from experiments in the 1980s, which associated protein kinase alpha (pka) and pkc to animal models of associative learning, opening an area of exploration for psychotropic development. The PKC family consists of several isoforms, including PKC alpha, beta1, beta1, gamma, delta and epsilon among others. In particular, PKC gamma (PRKCG) is highly brain-expressed and is singled out as a candidate for modulation in psychiatric illness. With hundreds of identified substrates, PRKCG affects multiple pathways relevant for regulation of neuronal health. In this review, converging lines of evidence are presented in the context of psychotropic drug action, which point to downregulation of PKC activity as a potential common mechanism across several psychiatric disorders. Using this mechanism through more targeted psychotropic action may then be used to develop agents that further ameliorate psychiatric symptom expression. Psychotropics including fluoxetine, tricyclics, lithium, valproate, ketamine and others are explored in relation to their effect of PKC, finding that across all drugs examined, a downregulation with chronic-but not acute-use constitutes their putative effect in ameliorating symptoms. This effect is compounded by findings that suggest that PKCs, and PRKCG in particular, promote neuroplastic effects by their downregulation. This effect is in contrast to PKC activators, which have been used in neurodegenerative disorders such as Alzheimer’s disease. Cross-disorder mechanisms need to continue to be explored in neuropsychiatric illness and targeted treatments developed in turn to address treatment-resistant conditions.